Lithium ion secondary battery

By using silicon carbon materials and lithium cobalt oxide in lithium-ion secondary batteries, and adding solid electrolytes and carboxylic acid ester compounds to the battery structure, the problems of poor cycling stability at high voltage and poor low-temperature discharge performance are solved, and high energy density and excellent battery performance are achieved.

CN119890407AActive Publication Date: 2025-04-25ZHUHAI COSMX BATTERY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411995763.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing high-energy density lithium-ion secondary batteries have poor cycling stability at high voltages, and the high-silicon doped batteries have poor discharge performance at low temperatures.

Method used

Silicon carbon material is used as the negative electrode active substance and lithium cobalt oxide is used as the positive electrode active substance. Solid electrolyte is added to the positive electrode sheet and carboxylic acid ester compounds are added to the electrolyte solution to improve the cycle stability and low-temperature discharge performance of the battery.

Benefits of technology

High energy density, excellent cycle stability and significantly improved low-temperature discharge performance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890407A_ABST
    Figure CN119890407A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium ion secondary battery. Comprising a positive plate, a negative plate and electrolyte, the charging cut-off voltage of the lithium ion secondary battery is greater than or equal to 4.5 V; the positive plate comprises a positive active coating, the positive active coating comprises a positive active substance and a solid electrolyte, the positive active substance comprises lithium cobalt oxide containing an element Al, and the mass content c1 of the element Al in the positive active coating is 6800ppm-15000ppm; the solid electrolyte comprises at least one of lithium aluminum titanium phosphorus oxide, lithium lanthanum zirconium tantalum oxide and lithium lanthanum titanium oxide; the negative plate comprises a negative active coating, and the negative active coating comprises a silicon carbon material; the mass content c2 of the element Si in the negative electrode active coating is 1.5%-20%; the electrolyte comprises a carboxylic ester compound. The battery provided by the invention has high energy density, excellent cycle stability and low-temperature discharge performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art

[0002] High capacity is the constant pursuit of batteries by users. Improving battery capacity is nothing more than increasing the gram capacity of positive and negative electrode materials, increasing the gram capacity of negative electrode materials by doping with silicon, and increasing the gram capacity of positive electrode materials by increasing the charge cut-off voltage. However, under high voltage, as the battery is charged and discharged, the lattice structure of the positive electrode material will collapse, resulting in poor cycle stability of the battery. In addition, due to the poor conductivity of silicon materials themselves, when silicon is doped in the negative electrode sheet, especially when the silicon content in the negative electrode sheet is high (for example, when the mass content of silicon in the negative electrode active coating is greater than or equal to 5%), the low-temperature discharge performance of the battery will be significantly reduced.

[0003] Therefore, it is necessary to improve both the cycle stability and low-temperature discharge performance of high energy density batteries. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of poor cycle stability and low-temperature discharge performance of high-energy-density batteries in the prior art, and to provide a lithium-ion secondary battery. The lithium-ion secondary battery of the present invention (hereinafter referred to as the battery) uses silicon-carbon material as the negative electrode active material, lithium cobalt oxide as the positive electrode active material, and is equipped with a higher charging cut-off voltage (for example, ≥4.5V) to achieve high energy density. At the same time, by regulating the content of the element Al in lithium cobalt oxide, the lattice structure of lithium cobalt oxide is stabilized, thereby improving the cycle stability of the battery. In addition, in view of the problem of poor low-temperature discharge performance of high-silicon-doped batteries (for example, when the mass content of silicon in the negative electrode active coating is greater than or equal to 5%), the low-temperature discharge performance of the battery is improved by adding a solid electrolyte to the positive electrode sheet and adding a specific solvent to the electrolyte.

[0005] The present invention provides a lithium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; the charging cut-off voltage of the lithium ion secondary battery is ≥4.5V; the positive electrode sheet comprises a positive electrode active coating, the positive electrode active coating comprises a positive electrode active substance and a solid electrolyte, the positive electrode active substance comprises lithium cobaltate, the lithium cobaltate contains element Al, and the mass content c1 of element Al in the positive electrode active coating is 6800ppm-15000ppm; the solid electrolyte comprises at least one of lithium aluminum titanium phosphorus oxide, lithium lanthanum zirconium tantalum oxide and lithium lanthanum titanium oxide; the negative electrode sheet comprises a negative electrode active coating, the negative electrode active coating comprises a negative electrode active substance, and the negative electrode active substance comprises a silicon-carbon material; the mass content c2 of element Si in the negative electrode active coating is 1.5%-20%; the electrolyte comprises a solvent, and the solvent comprises a carboxylic acid ester compound.

[0006] As the upper limit of battery charging voltage increases, the potential on the positive electrode side also increases, which poses a greater challenge to the stability of the lithium cobalt oxide lattice structure. On the one hand, the element Al can form an Al-O bond with the element O in lithium cobalt oxide, which has a larger bond energy, thereby effectively inhibiting the escape of lattice oxygen; on the other hand, Al 3+ The stability in the octahedral structure of lithium cobalt oxide is stronger, which makes it more difficult to transform lithium cobalt oxide into a monoclinic system, thereby reducing the kinetics of monoclinic formation and inhibiting the phase change of lithium cobalt oxide. Therefore, by regulating the mass content of element Al in the positive electrode active coating, the effect of stabilizing lithium cobalt oxide can be achieved. However, it does not mean that the greater the content of element Al, the better. This is because when the content of element Al increases, the gram capacity of lithium cobalt oxide will be reduced, thereby affecting the overall energy density of the battery. Therefore, it is necessary to regulate the mass content of element Al in the positive electrode active coating. When a specific range is met, it can ensure that the positive electrode sheet works stably at high voltage (for example, 4.5V and above), and ensure that the positive electrode sheet has sufficient capacity to play, and will not cause a loss of energy density due to excessive mass content of element Al.

[0007] The electrical conductivity of silicon-carbon materials is poor, and as the temperature decreases, the ionic conductivity of the electrolyte decreases significantly. Silicon-doped systems, especially systems with high silicon doping (for example, the mass content of silicon in the negative electrode active coating is greater than or equal to 5%), face the problem of being unable to discharge in extreme low temperature weather (for example, temperatures of -20°C and below). The ionic conductivity of solid electrolytes does not decrease significantly with decreasing temperature. Adding solid electrolytes to the positive electrode sheet can enable ions to be conducted along the solid electrolyte under extremely low temperature conditions, thereby replacing part of the electrolyte conduction path and ensuring that the battery can discharge normally under low temperature conditions. In addition, since the discharge process is a process of delithiation of the negative electrode and insertion of lithium in the positive electrode, in order to improve the low-temperature discharge performance of the battery, it is necessary to prioritize the lithium insertion rate on the positive electrode side. Therefore, solid electrolytes are added to the positive electrode sheet.

[0008] The above scheme can improve the cycle stability of the battery, and can improve the low-temperature discharge performance of the battery to a certain extent, but the improvement in low-temperature discharge performance has not met expectations. Therefore, it is necessary to further improve the low-temperature discharge performance of the battery. Carboxylate compounds have a lower melting point and viscosity than carbonate substances, which means that they can more easily remain in liquid form at low temperatures, thereby maintaining the electrical conductivity and discharge performance of the battery. And carboxylate compounds help to form a stable, dense and low-impedance SEI (Solid Electrolyte Interphase) film, which is crucial for the low-temperature discharge performance of the battery. Therefore, by adding carboxylate compounds to the electrolyte, the electrochemical properties of the electrolyte can be improved, the solvation structure of lithium ions is optimized, and a stable SEI layer is formed, thereby significantly improving the low-temperature discharge performance of the battery.

[0009] Through the above technical solution, the present invention has at least the following advantages compared with the prior art: the battery of the present invention can have high energy density, excellent cycle stability and low-temperature discharge performance.

[0010] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 1 (a) The grooves are arranged continuously; Figure 1 (b) The grooves are arranged in sections.

[0012] Figure 2 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 2 (a)- Figure 2 The two long sides of the groove in (c) are straight lines. Figure 2 The two long sides of the groove in (d) are curved.

[0013] Figure 3 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 3 (a) is the case where two adjacent long sides are straight and parallel. Figure 3 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 3 (c) is the case where two adjacent long sides are curved lines.

[0014] Figure 4 FIG. 1 is a schematic diagram showing the structure of a winding core in an example of the present invention.

[0015] Figure 5 The figure shows a schematic diagram of the structure of the positive electrode sheet in an example of the present invention, wherein Figure 5 (a) is a top view, Figure 5 (b) is a cross-sectional view along the thickness direction.

[0016] Figure 6 FIG. 1 is a schematic top view of the first surface of the positive electrode sheet in an example of the present invention. DETAILED DESCRIPTION

[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0018] The present invention provides a lithium ion secondary battery, which may include a positive electrode sheet, a negative electrode sheet and an electrolyte. The charging cut-off voltage of the lithium ion secondary battery is ≥4.5V, for example, 4.5V or 4.53V. The term charging cut-off voltage has a conventional meaning in the art, and generally refers to the maximum voltage value that the battery can safely reach during charging.

[0019] In the present invention, the positive electrode sheet may include a positive electrode active coating. The positive electrode active coating may include a positive electrode active material and a solid electrolyte. The positive electrode active material may include lithium cobalt oxide. Lithium cobalt oxide contains element Al, and the mass content c1 of element Al in the positive electrode active coating may be 6800ppm-15000ppm, for example, 6800ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm, 11000ppm, 12000ppm, 13000ppm, 14000ppm or 15000ppm.

[0020] In one example, c1 is 7100 ppm-10000 ppm.

[0021] In the present invention, the mass content c1 of the element Al in the positive electrode active coating can be obtained by testing by conventional methods in the art, for example, using an inductively coupled plasma-optical emission spectrometer (ICP-OES). The specific testing method is as follows: the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and immersed in a dimethyl carbonate (DMC) solvent for 12 hours; then the DMC solvent is used for elution to remove the lithium salt attached to the positive electrode sheet, and the positive electrode active coating is gently scraped off from the surface of the positive electrode current collector after calcination at 400° C. in a muffle furnace for 3 hours, and the mass content of the Al element is measured by ICP-OES (in ppm, i.e., one part per million). The specific operation method is performed in accordance with GB / T 30902-2014.

[0022] In the present invention, the chemical formula of lithium cobalt oxide can be Li a Co b M 1 c O2, where 0.8≤a≤1.05, 0.85≤b<1, 0 <c≤0.15,M 1 Including at least one of Al, Mg, Ti, Y, La, Ga, Ge, Sn, Si, Zr, Ca, Sb, In, Ni and Mn. Lithium cobalt oxide may include first particles and second particles, the average particle size of the first particles may be 0.3μm-7μm (for example, 0.3μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm or 7μm), and the average particle size of the second particles may be 7.5μm-40μm (for example, 7.5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm or 40μm). The use of lithium cobalt oxide with first particles and second particles having different average particle sizes can directly affect the filling effect of lithium cobalt oxide powder during compression through the difference in particle size distribution, thereby affecting the compaction density and electronic conductivity of lithium cobalt oxide, which is beneficial to improving the overall energy density and fast charging capability of the battery.

[0023] In the present invention, the average particle size of the first particles and the average particle size of the second particles can be tested and obtained by conventional methods in the field. For example, after the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and then soaked in DMC solvent for 12 hours, and then rinsed with DMC solvent to remove the lithium salt attached to the positive electrode sheet. After calcination at 400°C in a muffle furnace for 3 hours, the positive electrode active coating is gently scraped off the surface of the positive electrode current collector, and tested using a laser particle size analyzer. The particle size range of the first particle and the second particle can be obtained through the obtained curve.

[0024] In the present invention, the solid electrolyte may include at least one of lithium aluminum titanium phosphorus oxide, lithium lanthanum zirconium tantalum oxide and lithium lanthanum titanium oxide. The lithium aluminum titanium phosphorus oxide may be a super ion conductor type lithium aluminum titanium phosphorus oxide with a molecular formula of Li1+x Al x Ti 2-x (PO4)3, 0<x≤0.5. The lithium lanthanum zirconium tantalum oxide may be a garnet-type lithium lanthanum zirconium tantalum oxide, with a molecular formula of Li 7-y Ln3Z 2-y Ta y O 12 , 0≤y≤0.5. The lithium lanthanum titanium oxide may be a perovskite-type lithium lanthanum titanium oxide, with a molecular formula of Li 3z La 2 / 3-z TiO3, 0<z≤0.2. The solid electrolyte that meets the above molecular formula has strong ion conductivity and high dielectric constant, and has good affinity for electrolyte; using it for the positive electrode can improve the ion transmission capacity of the positive electrode, improve the dynamics of the battery, and thus make the battery have high energy density while having good low-temperature discharge performance and cycle stability.

[0025] In the present invention, the negative electrode sheet may include a negative electrode active coating. The negative electrode active coating may include a negative electrode active material, and the negative electrode active material may include a silicon-carbon material. The silicon-carbon material refers to a composite material including elemental carbon and elemental silicon, for example, a material formed by silicon and / or oxidized silicon filling (including partial filling or complete filling) in the pores of porous carbon.

[0026] In the present invention, the mass content c2 of element Si in the negative electrode active coating can be 1.5%-20%, for example, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0027] In one example, c2 is 4%-12%.

[0028] In the present invention, the mass content c2 of element Si in the negative electrode active coating can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and then the negative electrode sheet is treated at 400°C in an inert atmosphere for 2 hours after drying (for example, in a tubular furnace, under nitrogen or argon atmosphere), and the negative electrode active coating can be peeled off from the negative electrode current collector, and the negative electrode active coating is collected as a test sample. Using a thermogravimetric analyzer (for example, a TGA 550 thermogravimetric analyzer), the test sample amount is 5mg-15mg, and the temperature is increased from room temperature (25°C) to 900°C at a heating rate of 10°C / min in an air or oxygen atmosphere, and kept at 900°C for 40min, so that the non-silicon components in the negative electrode active coating are volatilized while the silicon can be fully oxidized to silicon dioxide. The remaining substance is the ash of the negative electrode active coating. The mass content of element Si in the negative electrode active coating can be calculated based on the mass of the ash. The calculation formula is as follows: mass content of element Si in the negative electrode active coating = 7×mass of ash / (15×mass of test sample).

[0029] In the present invention, the mass content of element Si in the silicon-carbon material can be 30%-80%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.

[0030] In the present invention, the electrolyte may include a solvent. The solvent may include a carboxylate compound. The carboxylate compound, for example, includes at least one of the following solvents substituted or unsubstituted with fluorine: ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate (PP), ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, and ethyl butyrate.

[0031] In the present invention, the mass content of the carboxylate compound in the electrolyte can be 10%-80%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.

[0032] In one example, the mass content of the carboxylic acid ester compound in the electrolyte is 20%-65%.

[0033] In the present invention, the mass content of the carboxylic acid ester compound in the electrolyte can be tested by conventional methods in the art, such as discharging the battery to 0% SOC, extracting the electrolyte in the battery, and testing it by gas chromatography (GC).

[0034] In the present invention, the solid electrolyte contains characteristic elements. The characteristic elements include at least one of Ti, Zr, La and Ta. The ratio of the mass content c3 of the characteristic element in the positive electrode active coating to the mass content c4 of the element Co in the positive electrode active coating can be 0.001-0.0055, for example, 0.001, 0.0015, 0.002, 0.0025, 0.003, 0.0035, 0.004, 0.0045, 0.005 or 0.0055.

[0035] In one example, the ratio of the mass content c3 of the characteristic element in the positive electrode active coating to the mass content c4 of the element Co in the positive electrode active coating is 0.0015-0.0035.

[0036] By regulating the ratio of the mass content of characteristic elements to element Co in the positive electrode active coating, the battery can take into account both low-temperature discharge performance and high-temperature stability. This is because the ratio of the two can explain the mass ratio of solid electrolyte and lithium cobalt oxide in the positive electrode active coating. When the ratio of the two is small (for example, less than 0.001), the mass content of solid electrolyte in the positive electrode active coating is relatively low. At this time, the solid electrolyte has limited improvement on the low-temperature discharge performance of the battery; and when the ratio of the two is large (for example, greater than 0.0055), the mass content of solid electrolyte in the positive electrode active coating is relatively high. Since the solid electrolyte is unstable in a high-temperature environment and is prone to gasification, when its content is high, it will have an adverse effect on the high-temperature performance of the battery.

[0037] In the present invention, the mass content c3 of the characteristic element in the positive electrode active coating can be 600ppm-3000ppm, for example, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2500ppm or 3000ppm.

[0038] In one example, c3 is 900 ppm-2000 ppm.

[0039] In the present invention, the mass content c3 of the characteristic element in the positive electrode active coating can be obtained by testing by conventional methods in the art, such as using ICP-OES. The specific testing method is as follows: discharge the battery to 0% SOC, disassemble and remove the positive electrode sheet, and soak it in DMC solvent for 12 hours; then rinse with DMC solvent to remove the lithium salt attached to the positive electrode sheet, calcine at 400°C in a muffle furnace for 3 hours, gently scrape the positive electrode active coating from the surface of the positive electrode collector, and measure the mass content of the characteristic element by ICP-OES (in ppm, i.e., one part per million). The specific operation method is carried out in accordance with GB / T 30902-2014.

[0040] In the present invention, "the mass content c3 of the characteristic element in the positive electrode active coating" refers to the mass content of at least one characteristic element in the solid electrolyte in the positive electrode active coating. For example, when the solid electrolyte is lithium lanthanum zirconium tantalum oxide, the lithium lanthanum zirconium tantalum oxide contains three characteristic elements La, Zr and Ta, then the mass content of at least one of the element La, the element Zr or the element Ta in the positive electrode active coating satisfies the above c3.

[0041] In the present invention, the mass content c4 of element Co in the positive electrode active coating can be 400000 ppm-750000 ppm, for example, 400000 ppm, 450000 ppm, 500000 ppm, 550000 ppm, 600000 ppm, 650000 ppm, 700000 ppm or 750000 ppm.

[0042] In one example, c4 is 500000 ppm-650000 ppm.

[0043] In the present invention, the average particle size of the solid electrolyte can be 500nm-3μm, for example, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm or 3μm.

[0044] In one example, the average particle size of the solid electrolyte is 1 μm-2 μm.

[0045] In the present invention, the average particle size of the solid electrolyte can be tested by conventional methods in the art, for example, after discharging the battery to 0% SOC, disassembling and removing the positive electrode sheet, soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the positive electrode sheet, using an argon ion milling instrument CP laser to cut the positive electrode sheet, and then using SEM to observe, measure at a rate of 5K, randomly select at least 20 solid electrolyte particles, measure the particle size of each solid electrolyte particle, and take the average value. If the number of solid electrolyte particles is less than 20 at a rate of 5K, then take a mirror image until 20 solid electrolyte particles are measured.

[0046] In the present invention, the electrolyte may also include vinylene carbonate (VC). VC is an unsaturated additive with good film-forming properties. It can preferentially reduce and decompose at the negative electrode to participate in the formation of the SEI film during the formation stage of the battery (therefore, the VC content in the electrolyte obtained by testing after the battery leaves the factory is significantly lower than the amount of VC added during the preparation of the battery), and plays a role in protecting the stability of the interface between the silicon-carbon material and the electrolyte. The SEI film derived from the reduction and decomposition of VC is rich in some highly elastic polymers, so it can help inhibit the volume expansion of the silicon-carbon material during the cycle process, while improving the cycle stability. Ensure the efficient migration of lithium ions in the SEI film, thereby improving the low-temperature discharge performance of the battery.

[0047] In the present invention, the mass content c5 of vinylene carbonate in the electrolyte can be 0.01%-15%, for example, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.

[0048] In the present invention, the mass content c5 of vinylene carbonate in the electrolyte can be obtained by testing by conventional methods in the art, such as discharging the battery to 0% SOC, extracting the electrolyte in the battery, and obtaining the content by GC testing.

[0049] In the present invention, the mass content c3 of the characteristic element in the positive electrode active coating and the mass content c1 of the element Al in the positive electrode active coating satisfy: 5×10 -6 ≤c3×c1≤2.5×10 -5 , for example, 5×10 -6 , 6×10 -6 ,7×10 -6 , 8×10 -6 ,9×10 -6 , 1×10 -5 , 1.5×10 -5, 2×10 -5 or 2.5 × 10 -5 .

[0050] In one example, 9.3×10 -6 ≤c3×c1≤1.5×10 -5 .

[0051] The mass content of element Al in the positive electrode active coating will affect the gram capacity of the positive electrode active material, and the low-temperature discharge capacity of the battery will decrease with the increase of the mass content of element Al. The content of characteristic elements directly affects the low-temperature discharge performance of the battery. To a certain extent, the low-temperature discharge capacity of the battery will increase with the increase of the content of characteristic elements. Therefore, when the two meet a specific relationship, the battery has a higher low-temperature discharge capacity, and the high-temperature performance will not be reduced due to excessive solid electrolytes.

[0052] In the present invention, the silicon-carbon material may include primary spherical particles. The average particle size of the primary spherical particles may be 1 μm-6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm.

[0053] In one example, the average particle size of the primary spherical particles is 3 μm-5 μm.

[0054] In the present invention, the average particle size of the primary spherical particles can be obtained by testing conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode sheet is cut by an argon ion milling instrument CP laser, and then observed by SEM (using the high voltage mode (Back-scattered Electrons BSE)). In this mode, the contrast of the silicon-carbon material is brighter (which can be used to distinguish the graphite material and the conductive agent in the negative electrode active coating), and at least 20 primary spherical particles are randomly selected at a 5K magnification, and the particle size of each primary spherical particle is measured to take the average value. If the number of primary spherical particles is less than 20 at a 5K magnification, then a mirror image is taken until 20 primary spherical particles are measured.

[0055] The commonly used silicon-carbon materials are block-shaped, and the average particle size is about 6μm-12μm. The relatively large average particle size results in poor conductivity of the particles. And because the hardness of the silicon-carbon material is relatively large, its compaction density is relatively small, which makes it difficult for the silicon content in the negative electrode active coating to reach more than 5%, which means that the improvement in the battery energy density is limited. The silicon-carbon material using primary spherical particles with an average particle size of 1μm-6μm not only has a high silicon content, that is, the silicon content in the negative electrode active coating is as high as 1.5%-20%, which can significantly improve the energy density of the battery; and its small particle size can improve the overall conductivity of the negative electrode sheet, thereby improving the low-temperature discharge performance of the battery.

[0056] In the present invention, the silicon-carbon material further comprises secondary spherical particles formed by a plurality of the primary spherical particles. The “several” means that the number of the primary spherical particles forming the secondary spherical particles is greater than or equal to 2.

[0057] Primary spherical particles with smaller particle sizes are beneficial to improving the energy density of the battery; however, due to their smaller particle size, the specific surface area is larger, resulting in a correspondingly higher risk of side reactions with the electrolyte, and poor stability. In order to reduce the occurrence of side reactions between the silicon-carbon material and the electrolyte, secondary spherical particles formed by a number of primary spherical particles are further added. Secondary spherical particles with larger particle sizes have a smaller specific surface area, so they have a lower risk of side reactions with the electrolyte and better stability.

[0058] In the present invention, the average particle size of the secondary spherical particles can be 3μm-20μm, for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.

[0059] In the present invention, the average particle size of the secondary spherical particles can be tested by conventional methods in the art, for example, after discharging the battery to 0% SOC, dismantling and removing the negative electrode sheet, soaking it in DMC solvent for 12 hours, and then rinsing it with DMC to remove the lithium salt attached to the negative electrode sheet, using an argon ion milling instrument CP laser to cut the negative electrode sheet, and then using SEM to observe (using high voltage mode), measuring at a magnification of 5K, randomly selecting at least 20 secondary spherical particles, measuring the particle size of each secondary spherical particle, and taking the average value. If the number of secondary spherical particles is less than 20 at a magnification of 5K, then take a mirror image again until 20 secondary spherical particles are measured.

[0060] In the present invention, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.1-0.9 of the total amount of the primary spherical particles and the secondary spherical particles, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9.

[0061] In one example, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.3-0.8 of the total amount of the primary spherical particles and the secondary spherical particles.

[0062] In the present invention, in the negative electrode active coating, the number of the primary spherical particles and the number of the secondary spherical particles can be tested and obtained by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode sheet is cut along the thickness direction of the negative electrode sheet using an argon ion milling instrument CP laser, and then observed using SEM (using high voltage mode) to obtain a mirror image of the cross section of the negative electrode sheet along the thickness direction, and observed at a magnification of 1K, and at least 20 mirror images of different cross sections are selected, and the number of primary spherical particles and the number of secondary spherical particles in each mirror image are counted respectively, and the average value is taken.

[0063] In the present invention, the negative electrode active material may further include a graphite material. The graphite material includes, for example, artificial graphite and / or natural graphite. The graphite material includes secondary particles. The secondary particles are formed by a plurality of primary particles. The “several” means that the number of the primary particles forming the secondary particles is greater than or equal to 2.

[0064] In the present invention, the average particle size of the secondary particles may be 6 μm-20 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.

[0065] By using a specific graphite material and adjusting the structure and particle size of the graphite material, the graphite material includes secondary particles composed of primary particles, and the average particle size of the secondary particles is 6μm-20μm, which can further improve the energy density of the battery. Compared with the graphite material of the primary particles, the secondary particles of the graphite material with a specific particle size can improve the energy density of the battery. Therefore, the graphite material has a high degree of matching with the specific silicon-carbon material, which is conducive to the improvement of the energy density of the battery.

[0066] In the present invention, the average particle size of the secondary particles can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, the negative electrode sheet is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode active coating is rinsed off from the negative electrode current collector with deionized water, and the filtrate is removed by centrifugation after ultrasonication, and dried, and the obtained sample is dispersed in deionized water containing nonylphenol polyoxyethylene ether (wherein the mass content of nonylphenol polyoxyethylene ether is 0.02%-0.03%) to form a mixture, ultrasonicated for 2 minutes, and then tested using a Malvern particle size tester, and the median particle size Dv50 data obtained is the average particle size of the secondary particles. Due to the specific composition and particle size of the graphite material and the silicon-carbon material in the present invention, the silicon-carbon material has little effect on the average particle size of the secondary particles of the graphite material, so the data obtained by the above test method is the average particle size of the secondary particles.

[0067] In the present invention, the lithium ion secondary battery may further include a separator. The separator may include an organic coating, the organic coating comprising polymer particles, the polymer particles containing at least one of a cyano group, an isocyano group, an isocyanate group and a triazine group. The polymer particles, for example, include at least one of polyacrylonitrile, nitrile rubber, 1,3,5-triazine-2,4,6-triamine, cyanuric acid, melamine and melamine thiocyanate.

[0068] In one example, the organic coating faces the positive electrode sheet.

[0069] When the organic coating is facing the positive electrode, the organic cyanide in the organic coating can diffuse to the surface of the positive electrode, stabilizing the crystal structure of metal ions and positive electrode active materials, reducing the release of active oxygen, and helping to improve the stability of the positive electrode active materials, thereby improving the cycle stability of the battery.

[0070] In the present invention, the mass content of element N in the organic coating may be 10.5%-55%, for example, 10.5%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or 55%.

[0071] In one example, the mass content of element N in the organic coating is 15%-35%.

[0072] In the present invention, the mass content of element N in the organic coating can be tested by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the diaphragm is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the diaphragm, and the adhesive layer on the outer surface of the organic coating is gently removed with tape (if no adhesive layer is provided on the outer surface of the organic coating, this step is omitted), the organic coating is observed using SEM, and then combined with an energy dispersive spectrometer (EDS), the particles in the organic coating are scanned at a magnification of 30K, at least 20 locations are selected, the mass content of nitrogen element is tested, and the average value is taken.

[0073] In the present invention, the diaphragm may further include a substrate layer and / or a glue layer. The substrate layer may include polyethylene, for example. The glue layer may include polyvinylidene fluoride (PVDF) and / or polymethyl methacrylate (PMMA).

[0074] In one example, the diaphragm includes the substrate layer, the organic coating layer located on one surface of the substrate layer, and the adhesive layer located on the other surface of the substrate layer.

[0075] In one example, the diaphragm includes the substrate layer, the organic coating layer located on one surface of the substrate layer, and the adhesive layer located on both outer surfaces of the diaphragm.

[0076] In the present invention, the thickness h of the organic coating may be 0.5 μm-4 μm, for example, 0.5 μm, 1 μm, 2 μm, 3 μm or 4 μm.

[0077] In one example, h is 1 μm-2 μm.

[0078] In the present invention, the outer surface of the negative electrode active coating may have a first concave portion. The negative electrode sheet includes a negative electrode current collector and the negative electrode active coating located on at least one side of the negative electrode current collector. The outer surface of the negative electrode active coating refers to the surface of the negative electrode active coating that is away from the negative electrode current collector.

[0079] A first recess is provided on the outer surface of the negative electrode active coating, which can provide a certain release space for the volume expansion of the negative electrode active material, reduce the extension of the negative electrode current collector caused by the volume expansion of the negative electrode active material, and is beneficial to further improve the cycle stability of the battery.

[0080] In the present invention, the first concave portion may include a concave hole or a groove. The first concave portion may be obtained by laser drilling or wire punching technology. When the first concave portion is a groove, the groove may be arranged continuously or in sections. Figure 1 FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 1(a) The grooves are arranged continuously; Figure 1 (b) The grooves are arranged in sections. As can be seen from the figure, the surface of the negative electrode sheet (i.e., the surface of the negative electrode active coating) has several grooves. Figure 1 In (a), the grooves are arranged continuously in the width direction of the negative electrode sheet. Figure 1 In (b), the grooves are arranged in sections in the width direction of the negative electrode sheet. It can be understood that Figure 1 Only the case where the groove is arranged along the width direction of the negative electrode sheet is given, and the groove can also be arranged along the length direction of the negative electrode sheet.

[0081] In the present invention, the depth of the first concave portion may be 5 μm-40 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. The depth of the first concave portion has the conventional meaning in the art, and refers to the vertical distance from the lowest point in the first concave portion to the surface of the negative electrode sheet. The depth of the first concave portion can be obtained by testing by conventional methods in the art, for example, using a 3D profiler to test the depths of all first concave portions or at least 20 first concave portions on the surface of the negative electrode active coating, and taking an average value.

[0082] In one example, the depth of the first concave portion is 15 μm-30 μm.

[0083] In the present invention, the width of the first concave portion may be 40 μm-200 μm, for example, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 150 μm or 200 μm.

[0084] In one example, the width of the first concave portion is 60 μm-100 μm.

[0085] When the first recess is a recessed hole, the width of the first recessed portion refers to the aperture of the recessed hole. The aperture of the recessed hole has the conventional meaning in this field. When the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a "regular circle", the aperture of the recessed hole is the diameter of the regular circle; when the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a non-"regular circle" (such as an ellipse or an irregular curved polygon), the aperture of the recessed hole is the diameter of an equivalent circle with an area equal to that of the non-"regular circle". The aperture of the recessed hole can be obtained by conventional means in this field, such as by testing the aperture of at least 20 recessed holes on the surface of the negative electrode active coating by a 3D profilometer and taking the average value.

[0086] When the first concave portion is a groove, the width of the first concave portion refers to the width of the groove. The width of the groove has a conventional meaning in the art. The positive projection of the groove on the surface of the negative electrode sheet includes two long sides, and the width of the groove refers to the average distance from one long side to another long side in the length direction or width direction of the negative electrode sheet. Figure 2 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 2 (a)- Figure 2 The two long sides of the groove in (c) are straight lines. Figure 2 The two long sides of the groove in (d) are curved. Figure 2 (a) and Figure 2 In (b), the two long sides are arranged in parallel, so that in the width direction of the negative electrode sheet, the vertical distance from any point on one long side to the other long side is equal. In this case, the width of the groove is the vertical distance L1 from any point on one long side to the other long side in the length direction or width direction of the negative electrode sheet. Figure 2 In (c), the two long sides of the groove are straight lines, but they are not set in parallel. Therefore, in the width direction, the size from any point on one long side to the other long side is not equal. In this case, the width of the groove can be averaged, that is, on one long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. Figure 2 In (d), the two long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the width of the groove can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 2 In (d), the two long sides are curved and do not exist. Figure 2 (c) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. The width of the groove can be obtained by conventional means in the art, such as by using a 3D profiler to test the width of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.

[0087] In the present invention, the spacing of the first recesses may be 0.5 mm-5 mm, for example, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm.

[0088] In one example, the interval between the first recesses is 0.8 mm-1.5 mm.

[0089] When the first concave portion is a concave hole, the spacing of the first concave portion refers to the spacing of the concave holes. The spacing of the concave holes has a conventional meaning in the art. It refers to the shortest distance between the edges of two adjacent concave holes on the surface of the negative electrode sheet. The spacing of the concave holes can be obtained by conventional means in the art, such as by SEM, selecting all or at least 10 groups of adjacent concave holes in the field of view of the electron microscope, measuring the spacing, and taking the average value.

[0090] When the first concave portion is a groove, the spacing of the first concave portion refers to the spacing of the grooves. It is understood that when there is only one groove on the surface of the negative electrode sheet, there is no spacing of the grooves. The spacing of the grooves has the conventional meaning in the art, which refers to the average distance between the two adjacent long sides of two adjacent grooves in the length direction or width direction of the negative electrode sheet. Figure 3 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 3 (a) is the case where two adjacent long sides are straight and parallel. Figure 3 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 3 (c) is the case where two adjacent long sides are curved. Figure 3 In (a), the two adjacent long sides are straight and parallel, so in the width direction, the distance from any point on one long side to the other long side is equal. In this case, the spacing of the grooves is the distance L2 from any point on one long side to the other long side in the width direction. Figure 3 In (b), the two adjacent long sides are straight lines, but they are not set in parallel. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can be averaged, that is, on a long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. Figure 3 In (c), the two adjacent long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 3 (c) The two long sides are curved, so there is no Figure 3 (b) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. The spacing of the grooves can be obtained by conventional means in the art, such as by using a 3D profilometer to test the spacing of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.

[0091] In the present invention, the positive electrode sheet may include a positive electrode current collector and the positive electrode active coating located on at least one side of the positive electrode current collector. The length of the positive electrode active coating located on the first surface of the positive electrode current collector is greater than the length of the positive electrode active coating located on the second surface of the positive electrode current collector. It can be understood that when the positive electrode sheet is coated, there are single-sided coating areas and double-sided coating areas. The single-sided coating area is the positive electrode current collector located in the area, and only one side of the surface has the positive electrode active coating; while the double-sided coating area is the positive electrode current collector located in the area, and both sides of the surface have the positive electrode active coating. This leads to the situation that the lengths of the positive electrode active coatings on the two sides of the positive electrode sheet are not equal. In the present invention, the side with a relatively longer length of the positive electrode active coating on the surface of the positive electrode current collector is defined as the first surface, and the side with a relatively shorter length of the positive electrode active coating is defined as the second surface. The area where the projections of the positive electrode active coating located on the first surface and the positive electrode active coating located on the second surface overlap in the thickness direction of the positive electrode sheet is the double-sided coating area, and the area where the above projections do not overlap is the single-sided coating area. Due to the special structure of the wound battery, usually the first surface faces the winding center of the winding core, and the second surface faces away from the winding center of the winding core.

[0092] In the present invention, the surface of the positive electrode active coating on the first surface has a second concave portion, and the surface of the positive electrode active coating on the second surface has a convex portion. Embossing treatment is performed on the surface of the positive electrode sheet to obtain a structure with concave portions on one side and convex portions on the other side.

[0093] The storage location of the electrolyte inside the battery is distributed in the gap between the core and the aluminum-plastic film and in the gap between the electrode layers. Interlayer storage mainly relies on the pores of the electrode and the capillary effect to slowly infiltrate, which takes a longer time and is more difficult to infiltrate than the gap between the core and the aluminum-plastic film. Therefore, the liquid storage capacity of the inner electrode of the core is significantly less than that of the outer electrode. The embossing process is used on the positive electrode to make one side have a concave part and the other side have a convex part, which can provide more liquid storage places, reduce the ion transmission distance, reduce the polarization of the positive and negative electrode sheets, and improve the overall charging speed of the battery.

[0094] In addition, the inventors of the present invention have conducted a stress analysis on the positive electrode active coating facing the winding center and away from the winding center in the winding core, and found that when a concave portion is provided on the first surface facing the winding center and a convex portion is provided on the second surface away from the winding center, it is not only beneficial to the structural stability of the positive electrode sheet itself, but also can provide a better buffer space for the volume expansion of the negative electrode sheet, which can improve the cycle life of the battery. Figure 4The following is a schematic structural view of a core in an example of the present invention. As can be seen from the figure, the core includes a negative electrode sheet 1 and a positive electrode sheet 2. The surface of the positive electrode active coating on the first surface has a second recess, and the surface of the positive electrode active coating on the second surface has a protrusion. The first surface faces the winding center of the core, and the second surface faces away from the winding center of the core.

[0095] In the present invention, the shape of the orthographic projection of the second recess and the protrusion on the surface of the positive electrode sheet is not limited, and it can be a circular shape, an oval shape, a linear shape (including a straight line or a wavy line), a polygonal shape, etc.

[0096] In the present invention, the positive electrode sheet includes a positive electrode tab welding area, a paste coating area, and an empty foil area. The empty foil area refers to the area on the positive electrode current collector where the positive electrode active coating is not coated except for the positive electrode tab welding area. The paste coating area includes a double-sided coating area and a single-sided coating area. As Figure 5 The following is a schematic structural view of a positive electrode sheet in an example of the present invention, where Figure 5 (a) is a top view, Figure 5 (b) is a cross-sectional view along the thickness direction. As can be seen from the figure, the positive electrode sheet includes a positive electrode tab welding area 3, a paste coating area 4, and an empty foil area 5, where the paste coating area 4 includes a double-sided coating area 10 and a single-sided coating area 20.

[0097] In one example, the second recess and the protrusion are located in the paste coating area.

[0098] In one example, the second recess and the protrusion are located in the double-sided coating area.

[0099] In one example, the second recess and the protrusion are located in the paste coating area and in the double-sided coating area.

[0100] In the present invention, the distance from the second recess to the edge of the positive electrode tab welding area is w1, 0 mm < w1 ≤ 10 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm.

[0101] In the present invention, the distance from the second recess to the edge of the first side of the paste coating area is w2, 2 mm ≤ w2 ≤ 40 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, 25 mm, 30 mm, 35 mm, or 40 mm. The first side is the side where the positive electrode tab welding area is provided.

[0102] In the present invention, the distance from the second concave portion to the edge of the second side of the paste application area is w3, where 2 mm ≤ w3 ≤ 25 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm or 25 mm. The second side is the side opposite to the side where the positive tab welding area is provided.

[0103] In the present invention, the distance from the second concave portion to the edge of the third side of the paste application area is w4, where 0 mm < w4 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm or 20 mm. The third side is the side of the paste application area close to the starting end of winding.

[0104] In the present invention, the distance from the second concave portion to the boundary line between the double-sided coating area and the single-sided coating area is w5, where 0 mm < w5 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm or 20 mm.

[0105] By controlling w1, w2, w3, w4 and w5, it is possible to ensure that the positive electrode sheet does not shed powder, which is beneficial to improving the cycle life of the battery.

[0106] As Figure 6 shown in the top view schematic diagram of the first surface of the positive electrode sheet in an example of the present invention, it can be seen from the figure that the first surface has a plurality of second concave portions 6. The distance from the second concave portion 6 to the edge of the positive tab welding area 3 is w1, the distance from the second concave portion 6 to the edge of the first side of the paste application area 4 is w2, the distance from the second concave portion 6 to the edge of the second side of the paste application area 4 is w3, the distance from the second concave portion 6 to the edge of the third side of the paste application area 4 is w4, and the distance from the second concave portion 6 to the boundary line between the double-sided coating area 10 and the single-sided coating area 20 is w5.

[0107] In the present invention, the depth of the second concave portion can be 3 μm - 40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. The height of the convex portion can be 3 μm - 40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.

[0108] In one example, the depth of the second concave portion is 10 μm-30 μm, and the height of the convex portion is 10 μm-30 μm.

[0109] In the present invention, the depth of the second concave portion and the height of the convex portion have the conventional meanings in the art, and the depth of the second concave portion refers to the vertical distance from the lowest point in the second concave portion to the surface of the positive electrode sheet. The height of the convex portion refers to the vertical distance from the highest point on the convex portion to the surface of the positive electrode sheet. The depth of the second concave portion and the height of the convex portion can be obtained by testing by conventional methods in the art, for example, by using a 3D profilometer, at least 20 second concave portions or 20 convex portions are selected on the surface of the positive electrode sheet, the depth of each second concave portion is measured, and the average value is taken to obtain the depth of the second concave portion; the height of each convex portion is measured, and the average value is taken to obtain the height of the convex portion.

[0110] In the present invention, the width of the second concave portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The width of the convex portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.

[0111] In one example, the width of the second concave portion is 1 mm to 3 mm, and the width of the convex portion is 1 mm to 3 mm.

[0112] In the present invention, when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the second concave portion is the diameter of the regular circle; when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the second concave portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. Similarly, when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the convex portion is the diameter of the regular circle; when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the convex portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. The width of the second concave portion and the width of the convex portion can be tested by conventional methods in the art, such as by a 3D profiler.

[0113] In the present invention, the spacing of the second concave portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The spacing of the convex portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.

[0114] In one example, the spacing between the second concave portions is 1 mm to 3 mm, and the spacing between the convex portions is 1 mm to 3 mm.

[0115] In the present invention, the spacing of the second concave portions refers to the shortest distance between the edges of the orthographic projections of two adjacent second concave portions on the surface of the positive electrode sheet, and similarly, the spacing of the convex portions refers to the shortest distance between the edges of the orthographic projections of two adjacent convex portions on the surface of the positive electrode sheet. The spacing of the second concave portions and the spacing of the convex portions can be obtained by testing by conventional methods in the art, for example, by using a 3D profilometer, selecting at least 10 groups of adjacent second concave portions or convex portions on the surface of the positive electrode sheet, measuring the spacing, and taking the average value.

[0116] In the present invention, the positive electrode active coating may further include a positive electrode conductor and a positive electrode binder, and the negative electrode active coating may further include a negative electrode conductor and a negative electrode binder. The positive electrode conductor and the negative electrode conductor may use a conductor conventionally used in the art. The positive electrode binder and the negative electrode binder may use a binder conventionally used in the art.

[0117] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent a difference in order.

[0118] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0119] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0120] The following examples are used to illustrate the lithium ion secondary battery of the present invention.

[0121] Example 1

[0122] Prepare the battery as follows:

[0123] (1) Preparation of positive electrode sheet

[0124] Lithium cobalt oxide (M 1Including Al), solid electrolyte (lithium aluminum titanium phosphorus oxide, chemical formula Li 1.3 Al 0.3 Ti 1.7 (PO4)3, with an average particle size of 1.5 μm), a positive electrode conductor (conductive carbon black) and a positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 96.039:0.961:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and a positive electrode slurry is prepared; the positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a 100 μm thick aluminum foil. m positive electrode sheet; a positive electrode tab welding area of ​​a fixed size is set on the paste coating area of ​​the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 20 mm), and the nickel tab is welded in the above-mentioned positive electrode tab welding area by laser; and then, after being passed through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is a circle;

[0125] Among them, the mass content c1 of element Al in the positive electrode active coating is 8273 ppm, the mass content c3 of characteristic element (Ti) in the positive electrode active coating is 1578 ppm, the mass content c4 of element Co in the positive electrode active coating is 580215 ppm, c3 / c4 is 0.0027, c3×c1 is 1.31×10 -5 The width of the second recess is 2 mm, the depth is 20 μm, and the spacing is 2 mm; w1 is 7 mm, w2 is 27 mm, w3 is 15 mm, w4 is 7 mm, and w5 is 7 mm.

[0126] (2) Preparation of negative electrode sheet

[0127] Artificial graphite (secondary particles), silicon-carbon material (the number of primary spherical particles accounts for 0.55 of the total number of primary spherical particles and secondary spherical particles, the average particle size of the primary spherical particles is 4.1 μm, and the mass content of element Si in the silicon-carbon material is 40%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 77:20:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the surfaces of both sides of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;

[0128] The mass content c2 of element Si in the negative electrode active coating is 8%, the width of the groove is 79.6 μm, the depth is 20.2 μm, and the spacing is 1.3 mm.

[0129] (3) Preparation of electrolyte

[0130] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; 45% of a carboxylic acid ester compound (PP) based on the total mass of the electrolyte is added to form a mixed solvent; 15% of fluoroethylene carbonate, 7.5% of VC (c5 is 7.5%) and 12.5% ​​of lithium hexafluorophosphate based on the total mass of the electrolyte are dissolved in the above mixed solvent to obtain an electrolyte.

[0131] (4) Preparation of diaphragm

[0132] 1,3,5-triazine-2,4,6-triamine is ground, and then evenly mixed with styrene-butadiene rubber and lithium polyacrylate in a mass ratio of 63:30:7, and NMP is added to obtain an organic coating slurry; the organic coating slurry is coated on one surface of a polyethylene film and dried (forming an organic coating with a thickness h of 1.3 μm); a PMMA adhesive layer is coated on the other surface of the polyethylene film, and a PVDF+PMMA adhesive layer is coated on the outer surface of the organic coating (the mass ratio of PVDF to PMMA is 7:3) to obtain a diaphragm, wherein the mass content of element N in the organic coating is 28%.

[0133] (5) Preparation of batteries

[0134] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core (wherein the organic coating faces the positive electrode sheet); and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.

[0135] Example 2

[0136] Prepare the battery as follows:

[0137] (1) Preparation of positive electrode sheet

[0138] Lithium cobalt oxide (M 1 Including Al), solid electrolyte (lithium aluminum titanium phosphorus oxide, chemical formula Li 1.3 Al 0.3 Ti 1.7(PO4)3, with an average particle size of 1.2 μm), a positive electrode conductor (conductive carbon black) and a positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 96.042:0.958:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and a positive electrode slurry is prepared; the positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a 100 μm thick aluminum foil. m positive electrode sheet; a positive electrode tab welding area of ​​a fixed size is set on the paste coating area of ​​the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 15 mm), and the nickel tab is welded in the above-mentioned positive electrode tab welding area by laser; and then, after being passed through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;

[0139] Among them, the mass content c1 of element Al in the positive electrode active coating is 7126ppm, the mass content c3 of characteristic element (Ti) in the positive electrode active coating is 1991ppm, the mass content c4 of element Co in the positive electrode active coating is 564282ppm, c3 / c4 is 0.0035, c3×c1 is 1.42×10 -5 The width of the second recess is 1 mm, the depth is 10 μm, and the spacing is 1 mm; w1 is 5 mm, w2 is 20 mm, w3 is 10 mm, w4 is 5 mm, and w5 is 5 mm.

[0140] (2) Preparation of negative electrode sheet

[0141] Artificial graphite (secondary particles), silicon-carbon material (the number of primary spherical particles accounts for 0.32 of the total number of primary spherical particles and secondary spherical particles, the average particle size of the primary spherical particles is 3 μm, and the mass content of element Si in the silicon-carbon material is 40%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 77:20:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the surfaces of both sides of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;

[0142] The mass content c2 of element Si in the negative electrode active coating is 8%, the width of the groove is 60.1 μm, the depth is 15.4 μm, and the spacing is 0.8 mm.

[0143] (3) Preparation of electrolyte

[0144] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; 20% of a carboxylic acid ester compound (PP) based on the total mass of the electrolyte is added to form a mixed solvent; 15% of fluoroethylene carbonate, 10% of VC (c5 is 10%) and 12.5% ​​of lithium hexafluorophosphate based on the total mass of the electrolyte are dissolved in the above mixed solvent to obtain an electrolyte.

[0145] (4) Preparation of diaphragm

[0146] 1,3,5-triazine-2,4,6-triamine is ground, and then evenly mixed with styrene-butadiene rubber and lithium polyacrylate in a mass ratio of 40:50:10, and NMP is added to obtain an organic coating slurry; the organic coating slurry is coated on one surface of a polyethylene film and dried (forming an organic coating with a thickness h of 1 μm); a PMMA adhesive layer is coated on the other surface of the polyethylene film, and a PVDF+PMMA adhesive layer is coated on the outer surface of the organic coating (the mass ratio of PVDF to PMMA is 7:3) to obtain a diaphragm, wherein the mass content of element N in the organic coating is 15%.

[0147] (5) Preparation of batteries

[0148] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core (wherein the organic coating faces the positive electrode sheet); and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.

[0149] Example 3

[0150] Prepare the battery as follows:

[0151] (1) Preparation of positive electrode sheet

[0152] Lithium cobalt oxide (M 1 Including Al), solid electrolyte (lithium aluminum titanium phosphorus oxide, chemical formula Li 1.3 Al 0.3 Ti 1.7(PO4)3, with an average particle size of 1.7 μm), a positive electrode conductor (conductive carbon black) and a positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 96.033:0.967:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and a positive electrode slurry is prepared; the positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a 100 μm thick aluminum foil. m positive electrode sheet; a positive electrode tab welding area of ​​a fixed size is set on the paste coating area of ​​the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 25 mm), and the nickel tab is welded in the above-mentioned positive electrode tab welding area by laser; and then, after being passed through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;

[0153] The mass content of Al in the positive electrode active coating is c1, which is 9986 ppm; the mass content of the characteristic element (Ti) in the positive electrode active coating is c3, which is 936 ppm; the mass content of Co in the positive electrode active coating is c4, which is 618542 ppm; c3 / c4 is 0.0015; c3×c1 is 9.35×10 -6 The width of the second recess is 3 mm, the depth is 30 μm, and the spacing is 3 mm; w1 is 9 mm, w2 is 34 mm, w3 is 20 mm, w4 is 10 mm, and w5 is 10 mm.

[0154] (2) Preparation of negative electrode sheet

[0155] Artificial graphite (secondary particles), silicon-carbon material (the number of primary spherical particles accounts for 0.79 of the total number of primary spherical particles and secondary spherical particles, the average particle size of the primary spherical particles is 4.9 μm, and the mass content of element Si in the silicon-carbon material is 40%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 77:20:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the surfaces of both sides of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;

[0156] The mass content c2 of element Si in the negative electrode active coating is 8%, the width of the groove is 99.2 μm, the depth is 29.5 μm, and the spacing is 1.5 mm.

[0157] (3) Preparation of electrolyte

[0158] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; then 65% of a carboxylic acid ester compound (PP) based on the total mass of the electrolyte is added to form a mixed solvent; 15% of fluoroethylene carbonate, 5% of VC (c5 is 5%) and 12.5% ​​of lithium hexafluorophosphate based on the total mass of the electrolyte are dissolved in the above mixed solvent to obtain an electrolyte.

[0159] (4) Preparation of diaphragm

[0160] 1,3,5-triazine-2,4,6-triamine is ground, and then evenly mixed with styrene-butadiene rubber and lithium polyacrylate in a mass ratio of 80:15:5, and NMP is added to obtain an organic coating slurry; the organic coating slurry is coated on one surface of a polyethylene film and dried (forming an organic coating with a thickness h of 2 μm); a PMMA adhesive layer is coated on the other surface of the polyethylene film, and a PVDF+PMMA adhesive layer is coated on the outer surface of the organic coating (the mass ratio of PVDF to PMMA is 7:3) to obtain a diaphragm, wherein the mass content of element N in the organic coating is 35%.

[0161] (5) Preparation of batteries

[0162] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core (wherein the organic coating faces the positive electrode sheet); and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.

[0163] Example 4 Group

[0164] This group of examples is used to verify the influence of the change of "the mass content c1 of the element Al in the positive electrode active coating".

[0165] This group of examples is carried out with reference to Example 1, except that c1 is changed, as follows:

[0166] Example 4a, c1 is 6852 ppm; wherein c3×c1 is 1.08×10 -5 ;

[0167] Example 4b, c1 is 14874 ppm; wherein c3×c1 is 2.35×10 -5 .

[0168] Example 5 Group

[0169] This group of examples is used to verify the impact of changes in the "solid electrolyte type".

[0170] This group of examples is carried out with reference to Example 1, except that the solid electrolyte is changed, as follows:

[0171] Example 5a, replacing lithium aluminum titanium phosphorus oxide with lithium lanthanum zirconium tantalum oxide, the chemical formula is Li 6.5 LqCy 1.5 Ta 0.5 O 12 In addition, in order to control the mass content c3 of the characteristic element to be close to that of Example 1, the ratio of the positive electrode slurry was adjusted: the mass ratio of lithium cobalt oxide, solid electrolyte, positive electrode conductive agent and positive electrode binder was 96.047:0.953:1:2, wherein the mass content c3 of the characteristic element (Zr) was 1676;

[0172] Example 5b, replacing lithium aluminum titanium phosphorus oxide with lithium lanthanum titanium oxide, the chemical formula is Li 30.3 La 0.567 TiO3, as above, the ratio of the positive electrode slurry was adjusted: the mass ratio of lithium cobalt oxide, solid electrolyte, positive electrode conductor and positive electrode binder was 96.032:0.968:1:2, among which the mass content c3 of the characteristic element (La) was 1628.

[0173] Example 6 Group

[0174] This group of examples is used to verify the influence of the change of "the mass content c2 of element Si in the negative electrode active coating".

[0175] This group of examples is carried out with reference to Example 1, except that c2 is regulated by changing the mass content of graphite material and silicon-carbon material in the negative electrode slurry, as follows:

[0176] Example 6a, artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 87:10:0.4:0.1:2.5, wherein c2 is 4%;

[0177] Example 6b, artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 67:30:0.4:0.1:2.5, wherein c2 is 12%;

[0178] Example 6c, artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 93:4:0.4:0.1:2.5, wherein c2 is 1.6%;

[0179] In Example 6d, artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 52:45:0.4:0.1:2.5, wherein c2 is 18%.

[0180] Example 7 Group

[0181] This group of examples is used to verify the influence of the change of "the mass content c3 of the characteristic element in the positive electrode active coating".

[0182] This group of examples is carried out with reference to Example 1, except that c3 is regulated by changing the content of the solid electrolyte in the positive electrode slurry, as follows:

[0183] Example 7a, the ratio of positive electrode slurry: the mass ratio of lithium cobalt oxide, solid electrolyte, positive electrode conductive agent and positive electrode binder is 96.031:0.969:1:2, c3 is 605ppm; c3 / c4 is 0.001, c3×c1 is 5.01×10 -6 ;

[0184] Example 7b, the ratio of positive electrode slurry: the mass ratio of lithium cobalt oxide, solid electrolyte, positive electrode conductive agent and positive electrode binder is 96.05:0.95:1:2, c3 is 2967ppm; c3 / c4 is 0.0051, c3×c1 is 2.45×10 -5 .

[0185] Example 8 Group

[0186] This group of examples is used to verify the influence of the change of "the product c3×c1 of the mass content c3 of the characteristic element in the positive electrode active coating and the mass content c1 of the element Al in the positive electrode active coating".

[0187] This group of examples is carried out with reference to Example 2 and Example 3, except that c3×c1 is adjusted by changing c1, as follows:

[0188] Example 8a was carried out in accordance with Example 2, except that c1 was 9875 ppm, c3×c1 was 1.97×10 -5 ;

[0189] Example 8b was carried out in accordance with Example 3, except that c1 was 7233 ppm, c3×c1 was 6.77×10 -6 .

[0190] Example 9

[0191] This example is used to verify the influence of “whether the second concave portion is located on the surface of the positive electrode active coating on the first surface and whether the convex portion is located on the surface of the positive electrode active coating on the second surface”.

[0192] The method is carried out in accordance with Example 1, except that the embossing treatment is performed from the second surface to the first surface, that is, the surface of the positive electrode active coating on the second surface has a second concave portion, and the surface of the positive electrode active coating on the first surface has a convex portion.

[0193] Example 10

[0194] This example is used to verify the influence of “no second concave portion and convex portion being provided on the surface of the positive electrode active coating layer”.

[0195] The same process is carried out as in Example 1, except that no embossing treatment is performed.

[0196] Embodiment 11

[0197] This embodiment is used to verify the influence of "whether the single-sided coating area has a second concave portion".

[0198] The method is carried out in accordance with Example 1, except that the embossing treatment is performed on the single-sided coating area and the double-sided coating area (avoiding the positive electrode tab welding area).

[0199] Example 12 Group

[0200] This group of embodiments is used to verify the impact of changes in "w1, w2, w3, w4 and w5".

[0201] This group of examples is carried out with reference to Example 1, except that w1, w2, w3, w4 and w5 are changed as follows:

[0202] In Example 12a, w1 is 0.5 mm, w2 is 2 mm, w3 is 2 mm, w4 is 0.5 mm, and w5 is 0.5 mm;

[0203] In Example 12b, w1 is 10 mm, w2 is 40 mm, w3 is 25 mm, w4 is 20 mm, and w5 is 20 mm.

[0204] Example 13 Group

[0205] This group of examples is used to verify the impact of changes in the "average particle size of primary spherical particles".

[0206] This group of examples is carried out with reference to Example 1, except that the control is performed by changing, as follows:

[0207] Example 13a, the average particle size of the primary spherical particles is 1.1 μm;

[0208] In Example 13b, the average particle size of the primary spherical particles is 6 μm.

[0209] Example 14 Group

[0210] This group of examples is used to verify the impact of changes in "the value of the number of primary spherical particles to the total number of primary spherical particles and secondary spherical particles".

[0211] This group of examples is carried out with reference to Example 1, except that the number ratio of spherical particles is changed once, as follows:

[0212] In Example 14a, all silicon-carbon materials are primary spherical particles, that is, the number of primary spherical particles accounts for 1 of the total number of primary spherical particles and secondary spherical particles;

[0213] In Example 14b, the number of primary spherical particles accounts for 0.11 of the total number of primary spherical particles and secondary spherical particles.

[0214] Embodiment 15

[0215] The method is carried out in accordance with Example 1, except that the artificial graphite is primary particles with an average particle size of 6.1 μm.

[0216] Example 16

[0217] This embodiment is used to verify the influence of changing the “type of the first recess”.

[0218] The process is carried out in accordance with Example 1, except that a laser is used to make recessed holes on the surface of the negative electrode sheet, wherein the width of the recessed holes is 85.2 μm, the depth is 20.1 μm, and the spacing is 0.5 mm.

[0219] Embodiment 17

[0220] This example is used to verify the influence of the change of "the mass content of the carboxylic acid ester compound in the electrolyte".

[0221] The same process is carried out as in Example 1, except that the content of PP is changed to 10%.

[0222] Example 18 Group

[0223] This group of examples is used to verify the impact of changes in "the mass content c5 of vinylene carbonate in the electrolyte".

[0224] This group of examples is carried out with reference to Example 1, except that c5 is regulated by changing the amount of vinylene carbonate added to the electrolyte, as follows:

[0225] Example 18a, no vinylene carbonate is added to the electrolyte, that is, c5 is 0;

[0226] Example 18b, c5 is 0.05%;

[0227] Example 18c, c5 is 15%.

[0228] Embodiment 19

[0229] This example is used to verify the impact of changes in the "organic coating".

[0230] The same method as in Example 1 was used, except that the organic coating was replaced with a boehmite ceramic coating of the same thickness.

[0231] Embodiment 20

[0232] This embodiment is used to verify the influence of "whether the organic coating is facing the positive electrode sheet".

[0233] The process is carried out in accordance with Example 1, except that the organic coating faces the negative electrode sheet.

[0234] Example 21 Group

[0235] This group of examples is used to verify the influence of the change of "the mass content of element N in the organic coating".

[0236] This group of examples is carried out with reference to Example 1, except that the mass content of element N in the organic coating is regulated by changing the substance or the composition of each substance in the organic coating, as follows:

[0237] Example 21a, 1,3,5-triazine-2,4,6-triamine is replaced by the same mass of polyacrylonitrile, wherein the mass content of element N in the organic coating is 10.5%;

[0238] In Example 21b, the mass ratio of 1,3,5-triazine-2,4,6-triamine, styrene-butadiene rubber and lithium polyacrylate is 94:5:1, wherein the mass content of element N in the organic coating is 55%.

[0239] Example 22 Group

[0240] This group of examples is used to verify the influence of the change of "the thickness h of the organic coating layer".

[0241] This group of examples is carried out with reference to Example 1, except that h is changed as follows:

[0242] Example 22a, h is 0.5 μm;

[0243] Example 22b, h is 4 μm.

[0244] The above embodiments all meet the following requirements: the average particle size of the first lithium cobalt oxide particles is 0.3 μm-7 μm, and the average particle size of the second lithium cobalt oxide particles is 7.5 μm-40 μm.

[0245] Except for Example 14a, all of the above embodiments satisfy that the average particle size of the secondary spherical particles of the silicon-carbon material is 3 μm-20 μm. Except for Example 15, all of the above embodiments satisfy that the average particle size of the secondary particles of the graphite material is 6 μm-20 μm.

[0246] Comparative Example 1

[0247] The process is carried out in accordance with Example 1, except that no solid electrolyte is added to the positive electrode sheet, that is, lithium cobalt oxide, positive electrode conductive agent and positive electrode binder are mixed in a mass ratio of 97:1:2, and NMP is added to prepare positive electrode slurry.

[0248] Comparative Example 2

[0249] This group of comparative examples is used to verify the influence of the change of "the mass content c1 of element Al in the positive electrode active coating".

[0250] This comparative example was carried out with reference to Example 1, except that c1 was changed, as follows:

[0251] Comparative Example 2a, c1 is 6354 ppm;

[0252] Comparative Example 2b, c1 is 17895 ppm.

[0253] Comparative Example 3

[0254] This comparative example is used to verify the influence of the change of "the mass content c2 of element Si in the negative electrode active coating".

[0255] Refer to Example 1, except that c2 is regulated by changing the mass content of graphite material and silicon-carbon material in the negative electrode slurry. Specifically, artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 37:60:0.4:0.1:2.5, wherein c2 is 24%.

[0256] Comparative Example 4

[0257] This comparative example is used to verify the effect of “not adding carboxylic acid ester compounds to the electrolyte”.

[0258] The process is carried out in accordance with Example 1, except that PP is not added to the electrolyte.

[0259] Test Case

[0260] (1) Volume energy density test

[0261] The batteries prepared in the examples and comparative examples were tested for volume energy density, and the specific test method is as follows:

[0262] The battery was charged to 4.5V at a current of 0.2C, then charged at a constant voltage until the current dropped to 0.02C, and then discharged at a current of 0.2C to 3.0V, with the discharged energy recorded as E; the thickness, width and length of the battery were measured and the product of the three was calculated to obtain the volume of the battery recorded as V. The calculation formula for volume energy density is VED = E / V, and the results are recorded in Table 1.

[0263] (2) Low temperature discharge test

[0264] The batteries prepared in the examples and comparative examples were subjected to low temperature discharge tests. The specific test methods are as follows:

[0265] At room temperature (25℃), charge the battery with constant current and voltage at 0.2C to 4.5V, cut off at 0.02C, let stand for 5 minutes, then discharge at 0.2C to 3.0V, record the discharge capacity C1, then charge the battery with constant current and voltage at 0.2C to 4.5V, cut off at 0.02C, put the fully charged battery into a -20℃ constant temperature box, let stand for 2 hours, then discharge at 0.2C to 3.0V, record the discharge capacity C2, C2 / C1 is the -20℃ 0.2C low-temperature discharge capacity retention rate, and record the results in Table 1.

[0266] (3) 45℃ high temperature cycle test

[0267] The batteries prepared in the examples and comparative examples were subjected to a 45°C high temperature cycle test. The specific test method is as follows:

[0268] Place it in a constant temperature room at 45℃ for 2h, charge it to 4.2V with 3C constant current, then charge it to 4.5V with 2C constant current and constant voltage, cut off at 0.05C, and place it for 10min; then discharge it to 3.0V with 0.7C, and repeat this cycle for 500 times. The discharge capacity of the battery at the 500th cycle is C1, and the discharge capacity of the battery at the first full charge is C0. Then C1 / C0 is the capacity retention rate after 500 cycles. The results are recorded in Table 1.

[0269] (4) High temperature storage test

[0270] The batteries prepared in the examples and comparative examples were subjected to high temperature storage tests. The specific test methods are as follows:

[0271] The battery was heated at room temperature (25°C) with a constant current and voltage of 0.2C to 4.5V, and cut off at 0.02C. The thickness h1 of the battery in the fully charged state was measured using a thickness tester at 600ppg. The battery was then placed at 85°C±2°C for 6 hours. The battery was taken out and the thickness h2 was immediately measured. (h2-h1) / h1 is the thickness expansion change rate. The results are recorded in Table 1.

[0272] Table 1

[0273]

[0274]

[0275] It can be seen from Table 1 that the battery of the present invention can have high energy density, excellent cycle stability, low-temperature discharge performance and high-temperature storage performance compared with the comparative example.

[0276] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; the charging cut-off voltage of the lithium-ion secondary battery is ≥4.5V; The positive electrode sheet comprises a positive electrode active coating, the positive electrode active coating comprises a positive electrode active material and a solid electrolyte, the positive electrode active material comprises lithium cobalt oxide, the lithium cobalt oxide contains element Al, and the mass content c1 of element Al in the positive electrode active coating is 6800ppm-15000ppm; the solid electrolyte comprises at least one of lithium aluminum titanium phosphorus oxide, lithium lanthanum zirconium tantalum oxide and lithium lanthanum titanium oxide; The negative electrode sheet comprises a negative electrode active coating, the negative electrode active coating comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material; the mass content c2 of element Si in the negative electrode active coating is 1.5%-20%; The electrolyte includes a solvent, and the solvent includes a carboxylic acid ester compound.

2. The lithium ion secondary battery according to claim 1, wherein The mass content c1 of element Al in the positive electrode active coating is 7100ppm-10000ppm; And / or, the mass content c2 of element Si in the negative electrode active coating is 4%-12%; And / or, the mass content of the carboxylic acid ester compound in the electrolyte is 10%-80%; preferably 20%-65%; And / or, the carboxylate compound includes at least one of the following fluorine-substituted or unsubstituted solvents: ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate and ethyl butyrate.

3. The lithium ion secondary battery according to claim 1 or 2, wherein: The solid electrolyte contains characteristic elements, and the characteristic elements include at least one of Ti, Zr, La and Ta; Preferably, the ratio of the mass content c3 of the characteristic element in the positive electrode active coating to the mass content c4 of the element Co in the positive electrode active coating is 0.001-0.0055; more preferably 0.0015-0.0035; Preferably, the mass content c3 of the characteristic element in the positive electrode active coating is 600ppm-3000ppm; more preferably 900ppm-2000ppm; Preferably, the mass content c4 of the element Co in the positive electrode active coating is 400000ppm-750000ppm; more preferably 500000ppm-650000ppm; Preferably, the average particle size of the solid electrolyte is 500 nm-3 μm; more preferably 1 μm-2 μm.

4. The lithium ion secondary battery according to claim 1 or 2, wherein: The electrolyte also includes vinylene carbonate; Preferably, the mass content c5 of vinylene carbonate in the electrolyte is 0.01%-15%.

5. The lithium ion secondary battery according to claim 1 or 2, wherein: The solid electrolyte contains characteristic elements, and the characteristic elements include at least one of Ti, Zr, La and Ta; The mass content c3 of the characteristic element in the positive electrode active coating and the mass content c1 of the element Al in the positive electrode active coating satisfy: 5×10 -6 ≤c3×c1≤2.5×10 -5 ; Preferably, 9.3×10 -6 ≤c3×c1≤1.5×10 -5 .

6. The lithium ion secondary battery according to claim 1 or 2, wherein: The lithium-ion secondary battery further comprises a separator, wherein the separator comprises an organic coating; the organic coating comprises polymer particles, wherein the polymer particles contain at least one of a cyano group, an isocyano group, an isocyanate group and a triazine group; Preferably, the polymer particles contain element N, and the mass content of element N in the organic coating is 10.5%-55%; more preferably 15%-35%; Preferably, the organic coating faces the positive electrode sheet; Preferably, the polymer particles include at least one of polyacrylonitrile, nitrile rubber, 1,3,5-triazine-2,4,6-triamine, cyanuric acid, melamine and melamine thiocyanate; Preferably, the thickness h of the organic coating is 0.5 μm-4 μm.

7. The lithium ion secondary battery according to claim 1 or 2, wherein: The silicon-carbon material comprises primary spherical particles; And / or, the mass content of element Si in the silicon-carbon material is 30%-80%; And / or, the negative electrode active material further includes graphite material.

8. The lithium ion secondary battery according to claim 1 or 2, wherein: The outer surface of the negative electrode active coating has a first concave portion; Preferably, the depth of the first concave portion is 5 μm-40 μm; Preferably, the width of the first concave portion is 40 μm-200 μm; Preferably, the spacing between the first recesses is 0.5 mm-5 mm.

9. The lithium ion secondary battery according to claim 1 or 2, wherein: The positive electrode sheet comprises a positive electrode current collector and the positive electrode active coating located on at least one side of the positive electrode current collector; the length of the positive electrode active coating located on the first surface of the positive electrode current collector is greater than the length of the positive electrode active coating located on the second surface of the positive electrode current collector; the area where the projections of the positive electrode active coating located on the first surface and the positive electrode active coating located on the second surface in the thickness direction of the positive electrode sheet overlap is a double-sided coating area, and the area where the projections do not overlap is a single-sided coating area; The surface of the positive electrode active coating layer located on the first surface has a second concave portion, and the surface of the positive electrode active coating layer located on the second surface has a convex portion; Preferably, the second concave portion and the convex portion are located in the double-sided coating area; Preferably, the positive electrode sheet comprises a positive electrode tab welding area, a paste coating area and a hollow foil area, and the second concave portion and the convex portion are located in the paste coating area; Preferably, the depth of the second concave portion is 3 μm-40 μm, the width of the second concave portion is 0.2 mm-8 mm, and the spacing between the second concave portions is 0.5 mm-8 mm; Preferably, the height of the convex portion is 3 μm-40 μm, the width of the convex portion is 0.2 mm-8 mm, and the interval between the convex portions is 0.5 mm-8 mm.

10. The lithium ion secondary battery according to claim 9, wherein The positive electrode sheet comprises a positive electrode tab welding area, a paste coating area and a blank foil area, wherein the paste coating area comprises the double-sided coating area and the single-sided coating area; The distance from the second recess to the edge of the positive electrode tab welding area is w1,0 mm <w1≤10mm; And / or, the distance from the second recess to the first edge of the paste coating area is w2, 2mm≤w2≤40mm, and the first edge is a side where the positive electrode tab welding area is arranged; And / or, the distance from the second concave portion to the second edge of the paste coating area is w3, 2mm≤w3≤25mm, and the second edge is a side opposite to a side where the positive electrode tab welding area is arranged; And / or, the distance from the second recess to the third side edge of the paste application area is w4, where 0 mm < w4 ≤ 20 mm, and the third side is the side of the paste application area close to the winding start end; And / or, the distance from the second recess to the boundary line between the double-sided coating area and the single-sided coating area is w5, where 0 mm < w5 ≤ 20 mm.

Citation Information

Patent Citations

  • High-voltage lithium-ion battery

    CN107331886A

  • Lithium ion secondary battery

    JP2017188404A

  • Lithium secondary battery

    WO2024228487A1

  • KR20240099081A